Working holiday makers in Australian horticulture: labour market effect, exploitation and avenues for reform. Issue 1 (2nd January 2018) - Reilly, Alexander; Howe, Joanna; van den Broek, Diane; Wright, Chris F.
ABSTRACT: Using a mixed-method analysis, this paper examines the effect of working holiday makers (WHMs) on the labour market for low-skilled work in the horticulture industry. Since the inception of the WHM visa in 1975, the horticulture industry has come to rely increasingly on WHMs as the core source of labour for picking and packing fruit and vegetables. This reliance has altered employers' expectations of labour flexibility, cost and productivity and has limited the role of local workers in the industry in many locations. At the same time, there is evidence of widespread exploitation of WHMs in the industry. There is a difficult policy challenge of how to address the problems of exploitation while maintaining a reliable labour supply for the industry. The article draws on the growing literature considering the role of temporary labour migration on national labour markets to frame the analysis of WHMs in Australian horticulture, and concludes with suggestions for how the horticulture labour market can be reformed through appropriate, targeted regulation of temporary migrants in the industry.